Case report: Fatal cerebral herniation caused by hypoglycemic due to mistaking glibenclamide in children - Song, Chunlan; Jia, Wanyu; Shi, Shengli; Li, Peng (Frontiers in Behavioral Neuroscience, 2023)
In recent years, the prevalence of diabetes in China has significantly increased, and glibenclamide is widely used as a basic hypoglycemic drug in China's primary clinical practice. There are many left-behind children in the grass-roots areas in China and various dangerous incidents of children taking drugs by mistake continue to occur. This article reports a case of hypoglycemia, coma, cerebral edema and fatal cerebral hernia caused by mistakenly ingesting glyburide in a child. This is the first reported case in China of a child who died from brain herniaton caused by accidental administration of glibenclamide. This case reminded that clinicians must comprehensively consider the cause of convulsions and coma in children with unknown causes, ask the history in detail and cannot ignore the risk of hypoglycemic convulsions and coma. When hypoglycemic is detected, high concentration of glucose should be given promptly to normalize blood glucose. When dealing with unexplained convulsions and comatose children, clinical pediatricians must be alert to the possibility of accidental medication.